The archive of the forgotten - Hackwith, A. J. (A novel from hell's library, 2020)
"In the second installment of this richly imagined fantasy adventure series, a new threat from within the Library itself could destroy those within it. The Library of the Unwritten in Hell was saved from total devastation, but hundreds of potential books were destroyed, and the dreams that were held within them will never be realized. When the remnants of those books begin to leak a strange ink, and damsels keep disappearing and reappearing in the Arcane Wing, former librarian Claire realizes that the challenges within the Library have only just begun. Claire and Brevity the muse are immediately at odds concerning how to treat the ink, but the power that it presents has not gone unnoticed. Verity, a representative from the Muses Corps, arrives at the Library to advise Brevity on what to do with the ink, while Claire and the angel Rami hunt for a lost companion. Brevity will have to decide where her allegiances lie, and that choice will have the potential to remake the Library itself"--